Study on the adsorption performance of underwater propeller-driven Bernoulli adsorption device. (15th December 2022) - Chen, Yanhu; Liu, Siyue; Zhang, Luning; Zheng, Peiyang; Yang, Canjun
Abstract: The universality and effectiveness of underwater adsorption devices still remain challenges in the application of underwater climbing robots. In this letter, a propeller-driven Bernoulli adsorption device (PBD) with both propulsion and adsorption functions is developed. For the purpose of understanding the working principle and adsorption performance of PBD, theoretical modeling, computational fluid dynamics (CFD) simulations and experiments are sequentially carried out. The study results elaborate the effects of several design parameters on the adsorption performance of PBD, and prove that PBD can obtain a considerable adsorption force with a low power consumption. Based on the study results, an underwater dual-mode operating robot is developed to verify the effectiveness of PBD. Laboratory pool experiment and dam field experiment are respectively conducted, both of which demonstrate the feasibility of PBD in engineering applications. Highlights: Multifunctional underwater propeller-driven Bernoulli adsorption device is developed. The adsorption mechanism and the effects of design parameters are studied. Negative pressure effect plate can greatly improve the adsorption force. The adsorption device performs well on the underwater dual-mode operating robot.